2023
DOI: 10.1109/access.2023.3336615
|View full text |Cite
|
Sign up to set email alerts
|

Superfast Scan of Focused X-Ray Luminescence Computed Tomography Imaging

Yile Fang,
Yibing Zhang,
Michael C. Lun
et al.

Abstract: X-ray luminescence computed tomography (XLCT) is a hybrid molecular imaging modality having the high spatial resolution of x-ray imaging and high measurement sensitivity of optical imaging. Narrow x-ray beam based XLCT imaging has shown promise for high spatial resolution imaging of luminescent targets in deep tissues, but the slow acquisition speed limits its applications. In this work, we have introduced a superfast XLCT scan scheme based on the photon counter detector and a fly-scanning method. The new scan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Under the fly-scanning scheme, the three photon counters constantly collected the pulse signals from each of the five PMTs in a short data collection window (10 ms) and the position information was recorded constantly, which dramatically reduced the linear scanning time. Details of the fly-scanning scheme are described in [9].…”
Section: Phantom Experimental Set-upmentioning
confidence: 99%
See 1 more Smart Citation
“…Under the fly-scanning scheme, the three photon counters constantly collected the pulse signals from each of the five PMTs in a short data collection window (10 ms) and the position information was recorded constantly, which dramatically reduced the linear scanning time. Details of the fly-scanning scheme are described in [9].…”
Section: Phantom Experimental Set-upmentioning
confidence: 99%
“…To perform multi-color XLCT imaging, we have synthesized biocompatible nanophosphors with bright and distinct x-ray luminescence spectra and compared them with commercially available nanophosphors [6]. Furthermore, we have shown that the scan time could be improved by introducing a fly-scanning scheme and a dual channel gated photon counter as data acquisition device [7], [8], [9]. However, so far there is no quantitative study of pencil beam XLCT in imaging x-ray excitable nanophosphor targets in deep scattering media.…”
Section: Introductionmentioning
confidence: 99%
“…In the past, most of our studies utilized a single sensitivity optical photon detector [12][14][17][18]. However, the collection efficiency of excited optical photons by a single detector channel is low, consequently limiting the sensitivity and accuracy of the reconstructed XLCT images, while we have demonstrated that it is sufficient to obtain acceptable XLCT images with a single detector.…”
Section: Introductionmentioning
confidence: 99%
“…Lun et al [11] reported the successful reconstruction of a phosphor target with a concentration as low as 0.01 mg/mL at a scanning depth of 21 mm. Fang et al [12] recently reported a superfast X-ray luminescence computed tomography (XLCT) scan scheme utilizing a photon counter detector and fly-scanning method, achieving a remarkable 28.6-fold increase in speed (43 seconds per transverse scan) compared to previous methods, while maintaining improved XLCT image quality. This rapid scanning approach offers a viable method for conducting 3D X-ray Luminescence Computed Tomography (XLCT) imaging.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation